Soft Tissue and Bone Sarcoma (2014)
Soft tissue and bone sarcomas disproportionately affect children, adolescents, and young adults. Although considered a rare disease, sarcomas continue to have a devastating effect on these patients and their loved ones, and their impact on our society far exceed their relatively low prevalence. Because of its rarity and heterogeneity, clinical decision making on management of sarcomas are often individualized and without a consensus treatment strategy. Furthermore, research to improve clinical outcomes are particularly challenging as sizeable studies are hard to produce. By improving our knowledge about the molecular biology of sarcomas, we hope to identify new treatment strategies and targets for further drug development. [...]